Higher prevalence of eating disorders among adolescent elite athletes than controls - Martinsen, M.; Sundgot-Borgen, J. (Medicine & Science in Sports & Exercise, 2013)
Purpose: The objective of this study is to examine the prevalence of eating disorders (ED) among female and male adolescent elite athletes and nonathletic controls.